2021
DOI: 10.1097/olq.0000000000001439
|View full text |Cite
|
Sign up to set email alerts
|

Finding the Gaps in Retesting for Chlamydia and Gonorrhea: Differences Across High-Volume Testing Departments in an Urban Health Care Setting

Abstract: Background:The Centers of Disease Control and Prevention guidelines recommend that all patients be retested 3 months after a positive chlamydia (CT) or gonorrhea (GC) result. However, retest rates are generally low, and only a quarter of patients return to clinic for retesting. This analysis explored retesting patterns in a high sexually transmitted infection (STI)/human immunodeficiency virus (HIV)-risk setting to illuminate gaps in adherence to guideline recommendations. Methods:Retrospective chart data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…The younger male Veteran population typically does not seek VA benefits as much as the older male population in VHA and may be less likely to follow-up regarding repeat testing 22 . Although not evaluated in this study, other studies found that those who have primary care providers, are followed by infectious diseases or obstetrics/gynecology, or were diagnosed in outpatient settings as opposed to inpatient or emergency department settings were more likely to have repeat testing performed 6,7,12 . Other reasons for low retesting rates may be clinicians not educating patients on the importance of retesting or a lack of systems to standardize follow-up care in those with CT/GC infection.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The younger male Veteran population typically does not seek VA benefits as much as the older male population in VHA and may be less likely to follow-up regarding repeat testing 22 . Although not evaluated in this study, other studies found that those who have primary care providers, are followed by infectious diseases or obstetrics/gynecology, or were diagnosed in outpatient settings as opposed to inpatient or emergency department settings were more likely to have repeat testing performed 6,7,12 . Other reasons for low retesting rates may be clinicians not educating patients on the importance of retesting or a lack of systems to standardize follow-up care in those with CT/GC infection.…”
Section: Discussionmentioning
confidence: 82%
“…22 Although not evaluated in this study, other studies found that those who have primary care providers, are followed by infectious diseases or obstetrics/gynecology, or were diagnosed in outpatient settings as opposed to inpatient or emergency department settings were more likely to have repeat testing performed. 6,7,12 Other reasons for low retesting rates may be clinicians not educating patients on the importance of retesting or a lack of systems to standardize follow-up care in those with CT/GC infection. To increase guideline compliance, a potential strategy in VHA could be to have a follow-up appointment automatically setup with the individual's primary care doctor for their repeat testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] Retesting rates in the United States remain low, however, with widely varying retesting estimates of 9% to 42% for male and 18% to 43% for nonpregnant female individuals. [10][11][12] Despite the presence of clinical guidelines recommending DOT, little research has assessed the effectiveness of DOT for chlamydia treatment. One study compared the time to treatment between individuals who underwent DOT versus those who had a prescription sent to a pharmacy, and found no significant difference between the 2 groups.…”
mentioning
confidence: 99%
“…Health organizations also recommend STI retesting 3 months after treatment because of the increased likelihood of sequalae such as pelvic inflammatory disease or infertility in patients who are reinfected or do not complete treatment 7–9 . Retesting rates in the United States remain low, however, with widely varying retesting estimates of 9% to 42% for male and 18% to 43% for nonpregnant female individuals 10–12 …”
mentioning
confidence: 99%